Hyperacoustic hypoacusis: A new pontine syndrome—Case report. (24th August 2017) - Noureldine, Mohammad Hassan A.; Kikano, Raghid; Riachi, Naji; Ahdab, Rechdi
ABSTRACT: We herein report a unique case of a lateral pontine demyelinating lesion presenting with unilateral sensorineural hearing loss and paradoxical ipsilateral hyperacusis. The association of unilateral hearing loss and ipsilateral hyperacusis is a rare manifestation of a central nervous system lesion. The paradoxical combination of these symptoms strongly suggests pontine dysfunction and prompts urgent neurological evaluation.